Acylated flavonol glycosides from Tagetes minuta with antibacterial activity - Shahzadi, Irum; Shah, Mohammad M. (Frontiers in Pharmacology, 2015)
Wild marigold (Tagetes minuta), a flowering plant of the family Asteraceae contains compounds of pharmaceutical and nutritional importance especially essential oils and flavonols. Identification, characterization of flavonols and determination of their antibacterial activity were major objectives of the current study. The isolation and purification of flavonols was accomplished using chromatographic techniques while structural elucidation was completed by LC-MS and NMR spectroscopy. The extracts and purified compounds were tested against various bacterial strains for antibacterial activity. A total of nineteen flavonols were isolated from this species. Of these, seventeen were of butanol and two of ethyl acetate extracts. Based on the concentration and purity, eight potential flavonols were selected and structurally elucidated. Four flavonols, 6-hydroxyquercetin 7-O-β-(6''-galloylglucopyranoside) (2), 6-hydroxykaempferol 7-O-β-glucopyranoside (5), 6-hydroxykaempferol 7-O-β-(6''-galloylglucopyranoside) (7), 6-hydroxyquercetin 7-O-β-(6''-caffeoylglucopyranoside) (9), were identified for the first time from T. minuta. Butanol and ethyl acetate extracts of flowers and seeds showed significant antibacterial activity against Micrococcus leteus, Staphylococcus aureus, Bacillus subtilis and Pseudomonas piket. Among the isolated flavonols only 1, 2 and 18 were found to possess significant antibacterial activity against M. luteus. The extracts and purified flavonols from T. minuta can be potential candidates for antibacterial drug discovery and support to ethnopharmacological use.